Quantitative assessment of the rheumatoid synovial microvascular bed by gadolinium-DTPA enhanced magnetic resonance imaging. Issue 3 (1st March 1998) - Gaffney, Karl; Cookson, John; Blades, Selina; Coumbe, Adam; Blake, David
Abstract : OBJECTIVE: To examine the relation between rate of synovial membrane enhancement, intra-articular pressure (IAP), and histologically determined synovial vascularity in rheumatoid arthritis, using gadolinium-DTPA enhanced magnetic resonance imaging (MRI). METHODS: Dynamic gadolinium-DTPA enhanced MRI was performed in 31 patients with knee synovitis (10 patients IAP study, 21 patients vascular morphometry study). Rate of synovial membrane enhancement was quantified by line profile analysis using the image processing package ANALYZE. IAP was measured using an intra-compartmental pressure monitor system. Multiple synovial biopsy specimens were obtained by a blind biopsy technique. Blood vessels were identified immunohistochemically using the endothelial cell marker QBend30 and quantified (blood vessel numerical density and fractional area). RESULTS: Median blood vessel numerical density and fractional area were 77.5/mm 2 (IQR; 69.3–110.7) and 5.6% (IQR; 3.4–8.5) respectively. The rate of synovial membrane enhancement (median 2.74 signal intensity units/s, IQR 2.0–3.8) correlated with both blood vessel numerical density ( r = 0.46, p < 0.05) and blood vessel fractional area ( r = 0.55, p < 0.02). IAP did not influence the rate of enhancement. CONCLUSIONS: Gadolinium-DTPA enhanced MRI may prove to be a valuable technique for evaluating drugs that influence angiogenesis.